Controlling Product Returns from Sales Demonstrations: Experiments with a Linear Programming Model - Schoinohoritis, Panagiotis (2006)
Purpose The dissertation initially displays the key issues of Reverse Logistics and product demonstrations. A company in order to achieve an efficient product demonstrations management it is important to integrate and synthesize its strategies and policies with a responsive Closed-Loop Supply Chain. In the balance of this dissertation the author will try to achieve an insight into an optimal product demonstrations management. Based upon empirical evidence, it discusses the integration and alignment of the demonstrations operations with the reverse supply chain activities for expensive and time-sensitive products, for the Hewlett Packard case. Methodology/approach At first with the aid of an Analytical model, valuable information will be revealed for the major tradeoffs as well as the optimal policies, but for a simplified problem environment. A Linear Programming model for discovering insights in key sensitivities, process dynamics etc. is then proposed, showing the optimal policies for product demonstrations. Findings The results obtained reveal that a key factor for a successful product demonstrations management is an effective and responsive Closed-Loop Supply Chain. It is therefore to be supposed that an efficient and strategically integrated products demonstrations management would improve the results of this firm and increase its competitive advantage. This integration supports the idea that controlling product demonstrations effectively is not an easy task. But it seems that it is essential for companies with substantial product returns from demonstrations. Originality This dissertation may present some originality in identifying optimal solutions in demonstrations planning. Keywords Supply Chain Management, Closed-Loop Chains, Product demonstrations, Linear-Programming, Hewlett-Packard Paper type Dissertation